Analytical hierarchy process approach for basic component and system integration in tactical surveillance unmanned aerial vehicles - Mohd Suhaimi Omar; Wan Hasrulnizzam Wan Mahmood; Noor Irinah Omar; Nur Azmina Muhammad Haris Ong; Abdurrahman Faris Indriya Himawan (Penerbit Universiti Kebangsaan Malaysia, 2025)
The purpose of the article is to analyze Unmanned Aerial Vehicle component weight, its impact on takeoff weight, and system development. Data was gathered through case studies, interviews, document reviews, and field observations at Company XYZ, supplemented by secondary sources. The Analytical Hierarchy Process (AHP) and Quality Function Deployment (QFD) guided component selection. UAV weight was reduced from 150kg to 120kg. The RONCZ1046 aerofoil was chosen for its aerodynamics, structural integrity, and manufacturability. Engine LMN was selected for its power, efficiency, and reliability. Flight tests and maintenance assessments validated UAV integration and performance. This research provides an insight into UAV weight optimization, design consideration and engine selection, supporting future advancements in UAV development.